Femtoscopic study of the proton-proton and proton-deuteron systems in heavy-ion collisions at the LHC - Acharya, S.; Aglieri Rinella, G.; Aglietta, L.; Agnello, M.; Agrawal, N.; Ahammed, Z.; Ahmad, S.; Ahn, S.U.; Ahuja, I.; Akbar, Z.; Akindinov, A.; Akishina, V.; et al. (Elsevier, 2025)
This work reports femtoscopic correlations of p–p (p–p) and p–d (p–d) pairs measured in Pb–Pb collisions at centerof-mass energy per nucleon √ 𝑠NN = 5.02 TeV in the ALICE Collaboration. A fit to the measured proton-proton correlation functions allows one to extract the dependence of the nucleon femtoscopic radius of the particleemitting source on the pair transverse mass (𝑚T ) and on the average charge particle multiplicity ⟨dNch∕d𝜂⟩ 1∕3 for three centrality intervals (0 − 10%, 10 − 30 %, 30 − 50%). In both cases, the expected power-law and linear scalings are observed, respectively. The measured p–d correlations can be described by both two- and threebody calculations, indicating that the femtoscopy observable is not sensitive to the short-distance features of the dynamics of the p-(p-n) system, due to the large inter-particle distances in Pb–Pb collisions at the LHC. Indeed, in this study, the minimum measured femtoscopic source sizes for protons and deuterons have a minimum value at 2.73+0.05 −0.05 and 3.10+1.04 −0.86 fm, respectively, for the 30–50% centrality collisions. Moreover, the 𝑚T -scaling obtained for the p–p and p–d systems is compatible within 1𝜎 of the uncertainties. These findings provide new input for fundamental studies on the production of light (anti)nuclei under extreme conditions.
Keywords: Multiplicity (mathematics); Observable; Deuterium; Centrality; Large Hadron Collider; RADIUS; Nucleon; Transverse plane; https://purl.org/pe-repo/ocde/ford#1.03.04